Odontogenic Cyst with Verrucous Proliferation Exhibiting Melanin Pigmentation - Nidhi Manaktala; Karen Boaz; Krupa Mehta Soni; Srikant Natarajan; Junaid Ahmed; Keshava Bhat; Nandita Kottieth Pallam; Amitha Juanita Lewis (Hindawi Limited, 2017)
Verrucous proliferation arising from odontogenic cysts is a rare entity. We report an unusual case of an infected odontogenic cyst with verrucous proliferation and melanin pigmentation in a 13-year-old male patient who presented with an intraoral swelling in relation to impacted teeth 26 and 27. The enucleated lesion was diagnosed as an odontogenic keratocyst and the patient died within two years of presentation due to multiple recurrences. The clinical, radiological, and microscopic features of the lesion are presented with an attempt to discuss the etiopathogenesis. The case hereby reported is uncommon with only eight cases reported in the literature.